Geographic access and use of health services in the detection of pulmonary tuberculosis (Research, Society and Development, 2021)
Pulmonary tuberculosis is a serious public health problem, and access to early detection of the disease is critical for control. Thus, the objective of this study was to analyze the geographic access and the use of health services for the detection of pulmonary tuberculosis. For this, we analyzed the distances between the home of people with tuberculosis and the health services used, from the georeferencing of addresses of households and health services. Facilitated access was considered to be those located in an area up to 800 meters away from the home and difficult access to those at a greater distance. Descriptive statistics and chi-square test with residue analysis were used. It was found that most people with tuberculosis had easy geographic access (91%), used the services with difficult access for the first care (74.6%) and to obtain the diagnosis (86.5%). Also, people with tuberculosis lived close to the primary health care units, allowing the residence to be in the territory of coverage of the units with family health strategy. Primary health care had the largest contribution with easy access to the first care and diagnosis. Thus, it is concluded that access to tuberculosis detection was facilitated by health services located up to 800 meters from the home, however, the majority of respondents use services with difficult access in both first care and diagnosis.